RADIKALISME WANITA DALAM FILM SITI - Bayu Wira Handyan; Hapsari Dwiningtyas Sulistyani (Interaksi Online, 2019)
Siti is one of the many movies that portray women with a perspective that is rarely found in Indonesia earlier movies. Women in Indonesia earlier movies are often represented as a figure that does not have a choice, always subject to the dominance and masculinity shown by men. This study aims to describe the radicalism of women in patriarchal Javanese culture represented in the Siti movie. This type of research is qualitative research with semiotic approach. The analytical techniques used in this study is based on the concept of The Codes of Television presented by John Fiske. In analyzing the moving object, Fiske analyzes it in three levels: Reality level, Representation level, and Ideology level. Reality and Representation levels are analyzed syntagmatically. While the level of ideology is analyzed paradigmatically. The results of this study indicate that Siti is a radical (a radical-cultural that also radical-libertarian). This can be seen through the elements of radicalism represented by Siti. These elements appear at the level of Reality, Representation, and Ideology. Siti is a manifestation of the representation of women that appears in Indonesian movies produced after reformation. As an active woman, she is able to escape the objectification of men, and able to become a subject whose can determine her own life. Siti's courage was not only shown when she appeared masculine and served as the main economic support of her family. However, Siti's courage was also displayed through her emphasis on feminine values in the community. Through emphasizing these feminine values, Siti scheming against her weaknesses as a woman who is in a patriarchal culture.